The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/7427131
|View full text |Cite
|
Sign up to set email alerts
|

A Small‐Sample Adaptive Hybrid Model for Annual Electricity Consumption Forecasting

Abstract: Annual electricity consumption forecasting is one of the important foundations of power system planning. Considering that the long-term electricity consumption curves of developing countries usually present approximately exponential growth trends and linear and accelerated growth rate trends may also appear in certain periods, this paper first proposes a small-sample adaptive hybrid model (AHM) to extrapolate the above curves. The iterative trend extrapolation equation of the proposed model can simulate the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Amina et al [15] implemented a novel fuzzy wavelet neural network model for electricity consumption forecasting in the power system of the Greek Island of Crete, which provided significantly better results. In [16], a small-sample adaptive hybrid model (AHM) based on trend extrapolation method was proposed to forecast electricity consumption in China from 1991 to 2014, which showed robustness to stochastic changes and obtained more precise forecasting results. Al-Ghandoor et al [17] presented an empirical model based on multivariate linear regression of time series for the Jordanian industrial sector, which identified the main influential factors of electricity consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Amina et al [15] implemented a novel fuzzy wavelet neural network model for electricity consumption forecasting in the power system of the Greek Island of Crete, which provided significantly better results. In [16], a small-sample adaptive hybrid model (AHM) based on trend extrapolation method was proposed to forecast electricity consumption in China from 1991 to 2014, which showed robustness to stochastic changes and obtained more precise forecasting results. Al-Ghandoor et al [17] presented an empirical model based on multivariate linear regression of time series for the Jordanian industrial sector, which identified the main influential factors of electricity consumption.…”
Section: Introductionmentioning
confidence: 99%
“…In the matter of energy demand, various forecasting models have been applied to predict the electricity consumption. Traditional methods such as regression analysis (RA), time series analysis, nonparametric method, and small-sample adaptive hybrid model as well as soft computing techniques such as fuzzy logic, genetic algorithm, and neural networks are being extensively used [12][13][14][15][16][17]. Support vector regression, ant colony, and particle swarm optimization are new techniques being adopted for energy demand forecasting.…”
Section: Introductionmentioning
confidence: 99%